Straits settlements Blue Book miscellanea (imports/exports) 1888-1889 vol.26-28 (Great Britain : Public Record Office, 1971)
Mengandungi'Report on the Blue Book for 1888';'Straits Settlements return of imports and exports for the year 1888';'Blue Book for the year 1889'.